NARASI KESEMBILAN WALI DALAM MENYEBARKAN AGAMA ISLAM DI INDONESIA DALAM BUKU MI - Abdul Gani Jamora Nasution; Wahyu Azhari; Khairina Janani; Shafa Azzahra Nurzal (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
Graphic novel is one of many communication mediums with a combination of visual and verbal that mutually reinforces one another. This work remains a novel but uses the style of storytelling like a comic, using many illustrations. Graphic novels tell their stories from the beginning to the end, therefore graphic novels tend to be longer than comics. The content or quality of the story is different; graphic novel features a story with a more detailed content so that reading it requires serious concentration to think and understand what the creator is trying to convey.The graphic novel of Wali Songo's da'wah story, created by Gerdi Wirata Kusuma in 2015, presents nine Wali Songo stories, which are then selected into two stories to be studied, namely Sunan Kudus and Sunan Kalijaga. The graphic novel discusses the brief history of Wali Songo's life, including Wali Songo's propagation method in spreading the teachings of Islam.This research uses qualitative content analysis method, with Scott McCloud's comic theory, namely using comic element in the forms of image selection, selection of flow, and choices of words, moments, and frames. This identification is divided into two aspects; visual and verbal. Visual in the form of sequences of images, point of view, and graphics. Verbal in the form of narrative text that resides in column panels or word bubbles.The result of this research indicates that visual and verbal use are interrelated, such as the use of shots related to narration, the use of narration to mention information that can not be conveyed visually or visual expressions that can not be described verbally. This visual and verbal combination that mutually reinforces one another shows that this graphic novel is able to show the story of the history of Wali Songo's method in spreading teachings of Islam through assimilation of education and cultural arts with symbolic visual observations. The graphic novel of Wali Songo's da'wah story tries to show its history visually and verbally that is easy to understand and is able to become a part of medium of education.